The implication of occupational stress toward employee job performance at Pejabat Setiausaha Kerajaan Negeri Perlis / Syaliati Samsudin - Samsudin, Syaliati (Faculty of Business and Management, 2018)
This research has been conducted to identify the implication of occupational stress toward employee job performance at Pejabat Setiausaha Kerajaan Negeri Perlis. There were four factors of occupational stress which are workload, poor working condition, role ambiguity and inadequate monetary reward. These four factors were used as the independent variable on the study, while employee job performance was designated as dependent variable. The objectives of the study were to identify the level of employee's job performance and to examine the relationship between occupational stress and employee job performance. To measure the relationship and the implication between both variables, Statiscal Package for Social Science (SPSS) is used. The method used for this study was correlational research in order to examine the relationship between both variables. This study focusing the scope for three units under development sector with 73 respondents as the sample size. The sample size is referred to the sample size for given population by Krejcie and Morgan (1970). The sampling technique used was stratified simple random sampling. The finding result shows that all the factor significant relationship towards employee job performance. In the end of the report, there were several recommendations suggested by the researcher for the future researcher and Pejabat Setiausaha Kerajaan Negeri Perlis. The recommendation will useful to the organization to upgrade the independent variables that affect the employee job performance.